A Study to Compare the Talent Management Practices in Indian It Sector: Effective talent management strategies in the Indian IT sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Research aims to establish effective talent management strategies to avert increasing staff turnover rates of IT companies. A comparison was made related to the talent management strategies prevailing in IT sector. Sample of 60 employers from HCL, Wipro, TCS, Infosys and Tech Mahindra were used for the study, and data was analysed using the factor analysis, Anova method and the descriptive analysis. Results showed that Exit interviews, hiring competitors’ employees and regular employees survey were considered to be best effective strategies for the talent management while rest of the strategies were perceived as moderately effective. Further, the perceptions of the employers towards the effectiveness of the talent management strategies were different except for the few strategies namely competitive salary structure, exit interviews, competitors’ employees and employees survey.